The trans/national study of culture : a translational perspective - Bachmann-Medick, Doris (Concepts for the study of culture ;, 2014)
This volume establishes key concepts for a trans/national expansion in the study of culture. Using translation as an analytical category, it explores what is translatable between nation-specific approaches such as British/American Cultural Studies, German Kulturwissenschaften and French Sciences Humaines. Theoretical reflections and case studies contribute to a new trans/national view of the study of culture within an entangled world society.